Effect of Printing Temperature on Mechanical and Viscoelastic Properties of Ultra-flexible Thermoplastic Polyurethane in Material Extrusion Additive Manufacturing - Gümüş, Ömer Yunus; İlhan, Recep; Canlı, Berat Enes (SPRINGER, 2022)
Material extrusion (ME) is one of the additive manufacturing methods and widely used to produce polymer-based parts. Thermoplastic polyurethane (TPU) is a relatively new material in ME. It has microdomains consisting of hard segments (HS) and soft segments (SS) in varying proportions. This structural complexity and weak interactions between HS and SS cause the properties of TPUs to become very sensitive to processing parameters such as temperature. In this study, the effect of printing temperature in a range of 170-250 degrees C on the physical, mechanical, and viscoelastic properties of ultra-flexible TPU (Shore A 60) samples was investigated. Furthermore, to elucidate the effect of the manufacturing method, a sample prepared by compression molding (CM) at 230 degrees C was used. Thermal transitions of the samples were analyzed by DSC. Increasing T-g values were observed in correlation with increased printing temperature. A relation between T-g and hardness values was thus established. In order to observe molecular weight (M) changes after printing, zero shear viscosities (eta(0)) of polymer solutions were examined and preserved M values up to 200 degrees C were detected. Mechanical properties of the samples were analyzed through tensile tests. Among the samples including CM, the highest tensile strength and elongation at break were 37.6 MPa and 921%, respectively, which was detected for the sample printed at 230 degrees C. Oscillation tests revealed that both entanglements and HS content influence storages modulus (G '). Among the printed parts, highest G ' value was measured at 220 degrees C printing temperature. This result was attributed to the synergistic effect of entanglement and HS. Furthermore, it is concluded that chain alignment has greater contribution on mechanical properties than M, whereas viscoelastic properties is more sensitive to M.
Keywords: additive manufacturing; hardness; material extrusion; mechanical properties; printing temperature; TPU; viscoelastic properties